RETRACTED: Ernest Hemingway’s A Farewell to Arms: A Critical Study of War and Its Negative Impact from An Ironic Perspective - Muhammad Dera Farhan Al-Fahdawi (Jurnal Pendidikan Humaniora, 2017)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Humaniora to article entitled “Ernest Hemingway’s A Farewell to Arms: A Critical Study of War and Its Negative Impact from An Ironic Perspective" Vol 5, No 3, pp. 140-144, September 2017. This paper has been found to be in violation of the Jurnal Pendidikan Humaniora Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in International Journal of English Literature and Social Sciences (IJELS), Vol. 2, No. 4 (Jul-August 2017), pp. 111-115, 2017, DOI: 10.24001/ijels.2.4.13, URL: http://ijels.com/detail/ernest-hemingway-s-a-farewell-to-arms-a-critical-study-of-war-and-its-negative-impact-from-an-ironic-perspective/ entitled "Ernest Hemingway’s A Farewell to Arms: A Critical Study of war and its negative impact From an Ironic Perspective".The document and its content has been removed from Jurnal Pendidikan Humaniora, and reasonable effort should be made to remove all references to this article.